PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING LOAN (NPL), DAN INFLASI TERHADAP PENYALURAN KREDIT UMKM PADA PERBANKAN DI PROVINSI RIAU PERIODE 2014.QI-2019.QIV - Shinta, Sulistyani Indah; Rita, Iyan Yani; Any, Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determines the influence of Third Party Funds (TPF), Non Performing Loan (NPL), and Inflation to MSME Credit Distribution on Banks in Riau Province period 2014.QI-2019.QIV. The data used in this study are quarterly data from 2014 to 2019. The analytical method used is descriptive quantitative and analyzed with multiple linear regression model of Ordinary Least Square (OLS) approach using the tools of the computer statistical program Eviews version 10. The research results obtained are TPF, NPL and inflation together (simultaneously) affect the distribution of MSME Credit with a significance level of 5%. Partially, TPF have a positive and significant effect on MSME Credit Distribution, Inflation have a negative and significant effect on MSME Credit Distribution, while NPL has a negative and not significant effect on MSME Credit Distribution. Variations of factors that affect MSME Credit Distribution are explained by the TPF, NPL, and inflation together have an effect of 83,48% (adjusted R2 = 0.8348) while the remaining 16,52% is explained by other variables not included in this study.Keywords: TPF, NPL, Inflation, and MSME Credit Distribution